Writing research differently - Margaret Malone; Jourdan Davis; Stephen Muecke; Karen Schwartz; Chantal Trudel; Liz Weaver (Gateways)
This themed volume explores writing research differently: both the social practices that might foster experimentation and participation and the semiotic innovations needed to articulate knowledge plurality in our published scholarly texts. This collection of community-based research articles explores the many ways in which the standard genre conventions of the research article – order, structure, headings, images and quotes – can be creatively called upon to make visible on the page other worlds, other futures, other ways of knowing and being. Together, they demonstrate that coherence and cohesion – clarity – come in more shapes and forms than generally admitted, and can be welcoming frameworks for the rarely admitted: hope, sustenance, complexity, conflict and change.